Blade root force measurements on vertical axis tidal turbine (Proceedings of the European Wave and Tidal Energy Conference, 2025)
In 2019, Hydroquest tested its first 1MW-rated full-scale tidal turbineat Paimpol-Bréhat site. The success of this deployment has enabled thecompany to launch the development of the next generation of turbines through the FloWatt and Verti-Lab projects. In these projects,the validation of the industrial development tools are based on comparisonsof experimental, numerical and in-situ data at both small and large scales.In this context, a 1:20 scale tidal turbine model, similar to the geometryof the demonstrator designed for deployment in the Alderney Race, istested under representative conditions in the wave and current circulatingtank of Ifremer. The experimental set-up specifically developed for thisproject enables synchronised measurements of performance (from the rotortorque), blade forces and flow characteristics (from 2D PIV measurement) tobe carried out.The paper aims to describe in-depth the effects of fluid-structure inter-actions between the hydrodynamic loads and the blades of the turbine. Tothis end, we will first detail the experimental setup based on the use of afull quadrirotor twin vertical axis tidal turbine model and a single rotor de-vice. Then, we will study the angular distribution of the blade forces andthe flow characteristics close to the blade for several configurations in orderto analyse the effect of the different parts of the model, the central structure and the gravity base, on the rotor dynamic behaviour. The comparison be-tween the quadrirotor and the single rotor cases will help to understand theangular repartition of the blade lift and drag forces. In this way,the dynamic stall, which is typical of vertical axis tidal turbines, can becharacterised from both the rotor mechanical behaviour and the dynamic ofthe flow around the blades. The trials are carried out in January 2025 and the data will be fully anal-ysed in February in order to be able to send the paper before end of March.